2017
DOI: 10.1177/0261018317701611
|View full text |Cite
|
Sign up to set email alerts
|

The re-signification of state-funded community development in Ireland: A problem of austerity and neoliberal government

Abstract: This article analyses the changing rationalities and techniques through which the Irish state seeks to govern community development; specifically, how the displacement of its flagship Community Development Programme by the Social Inclusion and Community Activation Programme has been justified and operationalised. Adopting a governmentality perspective, it explains how community development came to be constructed as an anti-poverty strategy and why it should also be understood as a ‘technology of government’. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…ETBs are public bodies with a statutory education function: they are funded by the state and through fees paid by individuals for courses. In contrast, both LDCs and Family Resource centres are locally based organisations that receive state funding, though this funding was cut significantly under austerity (Meade, 2018). Our review of settlement services thus identified some mainstreaming, but more evidence of services provided by a wide range of third sector organisations, many with limited, short-term and/or insecure sources of funding.…”
Section: The Role Of the Irish Government In The Provision Of Settlement Servicesmentioning
confidence: 91%
“…ETBs are public bodies with a statutory education function: they are funded by the state and through fees paid by individuals for courses. In contrast, both LDCs and Family Resource centres are locally based organisations that receive state funding, though this funding was cut significantly under austerity (Meade, 2018). Our review of settlement services thus identified some mainstreaming, but more evidence of services provided by a wide range of third sector organisations, many with limited, short-term and/or insecure sources of funding.…”
Section: The Role Of the Irish Government In The Provision Of Settlement Servicesmentioning
confidence: 91%
“…As discussed, some analyses have conceived activation as paradigmatic or illustrative of broad societal changes in the principles governing the functioning of the modern welfare state or contemporary society more generally (for example, Serrano Pascual and Magnusson, 2007). The concept of activation here is often not defined independently but expressed through sociological notions such as ‘citizenship’ – including the changing ‘state–citizenship’ relationship (for example, Clarke, 2005; Ludwig-Mayerhofer et al, 2014), ‘active citizenship’ (for example, Goul Andersen et al, 2005) or ‘social citizenship’ (for example, Meade, 2018) – ‘individualization’ (for example, Eversberg, 2016) or ‘individual autonomy’ (Bothfeld and Betzelt, 2011). While operating with a broad definition of a concept is principally unproblematic, it is not always clear in this branch of the literature if the concept of activation is distinct from, or an element of, these wider concepts, and, if so, how.…”
Section: Activation As a Concept In Social Policy Researchmentioning
confidence: 99%
“…A second form of marketisation of activation was the application of commissioning processes, tendering and SLAs to replace traditional block grant funding models used with not-for-profits delivering activation and commuity dvelopment related services. This occurred through a 2015 commissioning process for the Social Inclusion Community Activation Programme and through shifts from block grants to Service Delivery Agreements for Local Employment Services and Jobs Clubs (Meade, 2017). These measures were and remain controversial and interviews suggest that, consistent with experience in the UK, commissioning is associated with shifts towards a competition culture in sectors that were strongly collaborative (Taylor et al, 2016).…”
Section: Creating Markets For Public Employment Servicesmentioning
confidence: 99%